Specific Characteristics of Financial Convergence in The Region (Eurasian Journal of Research, Development and Innovation, 2023)
The article shows the specific features of financial convergence. It is justified that the development of financial convergence processes has a significant impact on the financial market. Development indicators of financial convergence in the digital economy have been developed